Patient‐reported outcome measures (PROMs): A review of generic and condition‐specific measures and a discussion of trends and issues - Kate Churruca; Chiara Pomare; Louise A. Ellis; Janet C. Long; Suzanna B. Henderson; Lisa E. D. Murphy; Christopher J. Leahy; Jeffrey Braithwaite (Wiley, 2021)
Abstract Background Patient‐reported outcome measures (PROMs) are questionnaires that collect health outcomes directly from the people who experience them. This review critically synthesizes information on generic and selected condition‐specific PROMs to describe trends and contemporary issues regarding their development, validation and application. Methods We reviewed academic and grey literature on validated PROMs by searching databases, prominent websites, Google Scholar and Google Search. The identification of condition‐specific PROMs was limited to common conditions and those with a high burden of disease (eg cancers, cardiovascular disorders). Trends and contemporary issues in the development, validation and application of PROMs were critically evaluated. Results The search yielded 315 generic and condition‐specific PROMs. The largest numbers of measures were identified for generic PROMs, musculoskeletal conditions and cancers. The earliest published PROMs were in mental health‐related conditions. The number of PROMs grew substantially between 1980s and 2000s but slowed more recently. The number of publications discussing PROMs continues to increase. Issues identified include the use of computer‐adaptive testing and increasing concerns about the appropriateness of using PROMs developed and validated for specific purposes (eg research) for other reasons (eg clinical decision making). Conclusions The term PROM is a relatively new designation for a range of measures that have existed since at least the 1960s. Although literature on PROMs continues to expand, challenges remain in selecting reliable and valid tools that are fit‐for‐purpose from the many existing instruments. Patient or public contribution Consumers were not directly involved in this review; however, its outcome will be used in programmes that engage and partner with consumers.